A Central American Success Story: Innovation in International Distance Education - Donald W. Poucher; Dave King (Journal of Applied Communications, 2014)
Based on actual workshop experiences, faculty at the Honduran Zamorano University in Central America created an effective, size-neutral, world-class distance education (e-learning) program for serving learners throughout Latin America through online and distance learning technology. The program is known as PAC @ D (Programa de Aprendizaje Continuo a Distancia or Life Long Learning Program at a Distance). It is administered by Zamorano’s global center for distance learning. The establishment of PAC @ D in 2010 was preceded by workshop efforts begun in 2004 by the authors. The workshop efforts focused on bridging the cultural uniqueness of educational programs in Latin America and the United States. The goal was to assist local faculty and staff at Zamorano University to build their own digital platform effectively and extend academic and outreach programs through that digital platform. The use of online and distance learning technologies can help extend intellectual capital beyond the limits of the physical campus in fulfilling the teaching, outreach/extension, and, to a limited extent, research missions. However, as we shall see in this professional paper, distance learning is more than turning on the technology with a click and a keystroke. At Zamorano, the development of PAC @ D required many hours of a full range of pedagogical and technological training, spread over 18 months. This professional development paper provides the rationale for PAC @ D, outlines its development, and provides suggestions for enhancing the educational experiences of distance learners.
Keywords: e-learning; distance learning; continuing education.